Improving Fruit and Vegetable Consumption: Use of Farm-to-Consumer Venues Among US Adults - Blanck, Heidi Michels (Centers for Disease Control and Prevention, 2011)
Improvements to the food environment including new store development and more farm-to-consumer approaches (ie, farmers' markets, roadside stands, pick-your-own produce farms, or community-supported agriculture programs) may aid Americans in making healthier dietary choices. We analyzed data from a subset of respondents (N = 1,994) in the National Cancer Institute's Food Attitudes and Behaviors Survey, a mail survey of US adults. We determined associations between primary grocery shoppers' region and sociodemographic characteristics and frequency of purchasing fruits and vegetables in the summer from farm-to-consumer venues. A little more than one-quarter (27%) of grocery shoppers reported a frequency of at least weekly use of farm-to-consumer approaches. Older adults and respondents who live in the Northeast were most likely to shop farm-to-consumer venues at least weekly, and no differences were found by sex, race/ethnicity, education, or annual household income. These findings suggest that farm-to-consumer venues are used by many Americans and could be expanded to increase access to fruits and vegetables.